Muka positif dan muka negatif dalam cerpen Al-Khimar Al-Qori karya Kamil Al-Kaylani berdasarkan perspektif Erving Goffman - Hidayah, Hildan Nurul (Maliki Interdisciplinary Journal, 2024)
This study aims to identify positive faces and negative faces in the short story Al-Khimar Al-Qori by Kamil Al-Kaylani. The research method used is a qualitative method. The primary data source comes from the reading text of the short story Al-Khimar Al-Qori. Data were analyzed using reading and note techniques. The focus of this research is limited by the dialogue between the 2 main characters, Raja and Juha in order to produce valid data with the theory of positive face and negative face from Erving Goffman’s perspective, narration acts as additional or complementary data. The results of this study are dialogues that contain 4 types of positive faces and 2 types of negative faces with a classification of 3 positive faces of the king and 1 positive face of Juha, 1 negative face of Juha and 1 negative face of the king. The role of positive face and negative face as a representation of the principle of politeness contained in a dialogue in a literary work is interesting because it is based on the perspective of a sociological figure to interpret a literary work more specifically and deeply